2019
DOI: 10.1016/j.jcis.2019.07.106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface curvature, grafting density and solvent type on the PEGylation of titanium dioxide nanoparticles

Abstract: a b s t r a c t TiO 2 nanoparticles (NPs) are attracting materials for biomedical applications, provided that they are coated with polymers to improve solubility, dispersion and biocompatibility. Conformation, coverage density and solvent effects largely influence their functionality and stability. In this work, we use atomistic molecular dynamics simulations to study polyethylene glycol (PEG) grafting to highly curved TiO 2 NPs (2-3 nm) in different solvents. We compare the coating polymer conformations on NP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 100 publications
5
46
0
Order By: Relevance
“…These parameters include the concentration, 8 the end group, 9 the monomer composition, 10 the ionic strength and type of the aqueous surrounding, 8 and, as recently demonstrated, the local monomer concentration determined by the polymer shell morphology, 8 , 11 which also is influenced by the nanoparticle curvature. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…These parameters include the concentration, 8 the end group, 9 the monomer composition, 10 the ionic strength and type of the aqueous surrounding, 8 and, as recently demonstrated, the local monomer concentration determined by the polymer shell morphology, 8 , 11 which also is influenced by the nanoparticle curvature. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“… evaluated the flow behaviour of titanium dioxide dispersions in the presence of 2‐hydroxyethyl cellulose (HEC), where they found that maximum yield stress decreased when the HEC concentration increased. According to Selli et al , coated TiO 2 nanoparticles with polymer improve the solubility, dispersion and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic coordinates of the Ti and O atoms in the nanoparticle, as obtained by simulated annealing at 300 K and full atomic relaxation with the DFTB method in ref ( 14 ) when 46 dopamine molecules are attached, were kept fixed during all classical MM-MD simulations by Cartesian restraints with force constant equal to 5000 kcal/mol/Å 2 , the same protocol used in refs ( 57 ) and ( 58 ). This DFTB-optimized structure was solvated with a pre-equilibrated simulation box containing 6386 qSPC/Fw 55 water molecules using the LEaP module.…”
Section: Methodsmentioning
confidence: 99%